The Influence of Business Legality, Entrepreneurial Mindset, and Digital Transformation on Increasing the Competitiveness of MSMEs in Buleleng Regency - Suardika, Ketut; Septiari, Ketut Fransiska (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to determine how the influence of Business Legality, Entrepreneurial Mindset and Digital Transformation on Increasing Competitiveness in Micro, Small and Medium Enterprises (MSMEs) in Buleleng Regency. This study uses a quantitative approach, with the data collection technique used is a questionnaire distributed with Google Form media and a physical questionnaire assisted by the PLUT KUMKM Buleleng assistant with a Likert scale measuring instrument, where those selected as respondents are MSME owners with a total of 100 business owners. The data analysis technique used in this study is a structural equation model ( Structural Equation Modeling SEM) based on Partial Least Square (PLS) using the SmartPLS application . The novelty of this study lies in variables that have not been widely studied such as business legality variables, entrepreneurial mindset, digital transformation and competitiveness. In addition, the novelty of this study is that there has not been any research that directly examines the influence of entrepreneurial mindset on increasing the competitiveness of MSMEs. The results of the study indicate that Business Legality, Entrepreneurial Mindset , and Digital Transformation have a positive and significant effect on Increasing the Competitiveness of MSMEs. The research findings indicate that ownership of business legality, entrepreneurial mindset and carrying out digital transformation can increase competitiveness so that MSMEs are able to survive and continue to grow. The results of this study offer insights, valuable suggestions and provide solutions to problems related to increasing the competitiveness of MSMEs. Thus, the research findings can be a guideline for decisions for MSMEs and future government policies to help overcome the problems of MSME competitiveness .